Life history traits and historical comparison of blue whiting (Micromesistius poutassou) growth performance from the western Pomo/Jabuka Pits area (central Adriatic Sea) - Calì, Federico; La Mesa, Mario; Donato, Fortunata; Mazzoldi, Carlotta; Martinelli, Michela; Santojanni, Alberto (Frontiers in Marine Science, 2023)
Although fishing is considered the primary cause of the decline in fish populations, increasing evidence of the significant role of climate change has been provided recently in the Mediterranean Sea, which shows one of the highest warming trends in the world. In this area, the most important environmental driver is represented by the increase in seawater temperature. Though several studies have addressed the effects of sea warming on thermophilic species, little attention has been paid to cold-water species. Among these, blue whiting (Micromesistius poutassou) constitutes one of the most important traditional fisheries resources in the northern part of the basin, particularly in the central Adriatic Sea. This area has experienced intense fishing exploitation by the Italian and Croatian fishing fleets. Since 2015, the Pomo/Jabuka Pits area, the fleets’ main fishing ground, has been subject to a series of fishing regulations over time and space. In the present study, we investigated the age structure and growth performance (by means of otoliths) of blue whiting, comparing samples collected during 1985–86 and 2020–21 in the Pomo/Jabuka Pits. Our results show that the 2020–21 blue whiting specimens had a lower length-at-age compared to 1985–86. The asymptotic length estimate decreased from 29 cm TL in 1985–86 to 25 cm TL in 2020–21. The pattern observed might be related to a modification in the cold and dense water formation dynamics in the northern Adriatic Sea, as a consequence of climate change, resulting in higher temperatures and lower nutrient and oxygen exchange, which may have hampered the optimal growth of the species. Moreover, data on the historical trend of landings from the Adriatic Sea reveals a clear decline in catches starting from 2000 onwards. Although the introduction of a fishing ban in the Pomo/Jabuka Pits was an important milestone, the abundance of this species in the area remains at low levels, highlighting a potentially alarming situation for the stock of blue whiting in the central Adriatic Sea.